Genetic evidence for a protein kinase A/cubitus interruptus complex that facilitates processing of cubitus interruptus in Drosophila. - Kiger, J A (2001)
Hedgehog (Hh) activates a signal transduction pathway regulating Cubitus interruptus (Ci). In the absence of Hh, full-length Ci (Ci-155) is bound in a complex that includes Costal2 (Cos2) and Fused (Fu). Ci-155 is phosphorylated by protein kinase A (PKA), inducing proteolysis to Ci-75, a transcriptional repressor. Hh signaling blocks proteolysis and produces an activated Ci-155 transcriptional activator. The relationship between PKA and the Ci/Cos2/Fu complex is unclear. Here we examine Hh target gene expression caused by mutant forms of PKA regulatory (PKAr) and catalytic (PKAc) subunits and by the PKAc inhibitor PKI(1-31). The mutant PKAr*, defective in binding cAMP, is shown to activate Hh target genes solely through its ability to bind and inhibit endogenous PKAc. Surprisingly, PKAcA75, a catalytically impaired mutant, also activates Hh target genes. To account for this observation, we propose that PKAc phosphorylation targeting Ci-155 for proteolysis is regulated within a complex that includes PKAc and Ci-155 and excludes PKI(1-31). This complex may permit processive phosphorylation of Ci-155 molecules, facilitating their processing to Ci-75.